Pelvic organ prolapse management. Issue 2 (June 2020) - Fleischer, K; Thiagamoorthy, G
Pelvic organ prolapse describes the loss of support and subsequent descent of pelvic organs into the vagina. It is common, affecting up to 50% of parous women, and can be accompanied by a number of burdening symptoms. Prolapse has been thrown into the spotlight secondary to mesh-related complications. There are a number of effective treatment options to consider when managing pelvic organ prolapse and most do not require mesh. Patients' choice, comorbidities and likelihood of treatment success should be considered when making decisions about their care. Vaginal mesh surgery is currently on hold in the UK and even prior to this there has been a reduction both in the number of all prolapse surgeries and the number of women seeking surgery to manage their symptoms. This article reviews the current evidence for the management of pelvic organ prolapse, providing an update on the current state of mesh in prolapse surgery and summarises the key evidence points derived from the literature.